Effect of Related Party Transaction and Tax Haven Utilization on Tax Avoidance Moderated by Country-by-country Reporting - Romulo*, Cesar Samuel; Dalimunthe, Zuliani (Riwayat: Educational Journal of History and Humanities, 2024)
This research investigates the influence of Related Party Transactions and Tax Haven Utilization on Tax Avoidance with and without Country-by-Country Reporting regulations, which were introduced in Indonesia at the end of 2016, as moderating variables. This research uses a purposive sampling method as sample selection. The data in this study was collected from the financial reports of 96 multinational companies registered between 2012 and 2021. To test the hypothesis, this study used regression with Random Effect Model. The results of this research are that Tax Haven Utilization has a significant effect on Tax Avoidance and Related Party Transactions have no effect on Tax Avoidance. Other results show that Country-by-Country Reporting regulations are unable to moderate the influence of Related Party Transactions and Tax Haven Utilization on Tax Avoidance. The findings of this research provide recommendations for the government to launch CbCR regulations in order to prevent tax avoidance through mechanisms for utilizing tax havens and related party transactions as well as increasing understanding of the principles of implementing CBCR.